THE EFFECT OF USING AI ON STUDENTS' MOTIVATION AND ANXIETY IN LEARNING ENGLISH - Syifauddin, Muhammad; Yuliansyah, Ardian Ridho (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2023)
The background of this research focuses on the growing use of artificial intelligence (AI) in the learning process, particularly in English language learning. The use of AI is expected to have a positive impact on students' motivation and anxiety. However, there are concerns that the application of this technology can also pose new challenges for students, such as increased anxiety in learning. This study aims to analyze the effect of AI on students' motivation and anxiety in learning English. This study used a quantitative method with a survey approach. Data were collected through questionnaires distributed to students involved in learning English using AI. The data analysis technique used was regression analysis to examine the relationship between the use of AI and students' motivation and anxiety levels. The results showed that the use of AI in English language learning significantly increased students' motivation. However, the study also found that the use of AI can lead to increased anxiety levels among students, especially for those who are less familiar with the technology. These findings indicate the need for a balanced approach in the implementation of AI in learning, so as to maximize the benefits without causing adverse side effects.